1990
DOI: 10.1093/infdis/161.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia trachomatis Antigens in Urine as an Alternative to Swabs and Cultures

Abstract: By using commercially available spectrophotometric and immunofluorescent immunoassays, Chlamydia trachomatis antigens were detected in first-void urine (FVU) sediments from 224 men attending a sexually transmitted disease clinic at a frequency of 81.6%-86.8% compared with 86.8% (33/38) positive by urethral swab culture (P less than .05). Endocervical cultures from 228 women attending a gynecology clinic yielded 92.3% (12/13) positive compared with 61.5%-76.9% for urine samples in three antigen-detection assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 10 publications
0
62
0
Order By: Relevance
“…1-22 Paul and Caul2' have advocated testing an early morning specimen because it should contain more chlamydial antigen than a FVU sample collected "on the spot" as recommended by Chernesky et al 20 Thomas et a122 found that there was no difference in sensitivity between the two timings. All authors agree that there should be a long enough delay (2 to 4 hours) between the last void and the collection of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…1-22 Paul and Caul2' have advocated testing an early morning specimen because it should contain more chlamydial antigen than a FVU sample collected "on the spot" as recommended by Chernesky et al 20 Thomas et a122 found that there was no difference in sensitivity between the two timings. All authors agree that there should be a long enough delay (2 to 4 hours) between the last void and the collection of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…This has the added advantage that simultaneous testing can be performed for other pathogens like Neisseria gonorrhea as well as being non-invasive. However, the yield on urine samples are greater if it is a first-catch sample obtained 1 to 2 hours after prior urination, to so increase the amount of columner epithelial cells [45,46]. If sampling is performed in excess of 3 hours after last void, specificity and sensitivity is reduced in females, but in male patients, controversy still exists [47,48].…”
Section: Sampling For Non-culture-based Testingmentioning
confidence: 99%
“…Urine specimens are not, however, free from concerns about adequacy, since test manufacturers specify that urine specimens should be collected as first catch, should be of appropriate volume, and should be obtained within no less than 1 to 2 h of previous urination. In contrast to nucleic acid amplification tests, culture of urine specimens has historically not been useful, and antigen detection tests for urine have been relatively insensitive compared to DNA amplification tests, performing best with urine specimens from symptomatic males (35,40). Nucleic acid amplification testing with urine specimens from females can also detect cervical infections (111), presumably as a result of the urine washing over mucosal surfaces that have been contacted by cervical or vaginal secretions during collection.…”
Section: Specimen Collectionmentioning
confidence: 99%